2014
DOI: 10.15376/biores.9.4.6817-6830
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of the Optimum Softwood Lignin Content for the Production of Bioethanol in a Repurposed Kraft Mill

Abstract: Kraft pulping is one possible pretreatment for softwood to economically produce bioethanol. This work evaluates the techno-economic potential of using the kraft process for producing bioethanol from softwoods in a repurposed or co-located kraft mill. Pretreated loblolly pine was enzymatically hydrolyzed at low enzyme dosages of 5 and 10 FPU/g of substrate. Pretreated residue with 13% lignin content had the highest sugar recovery, 32.7% and 47.7% at 5 and 10 FPU/g, respectively. The pretreated residues were oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Green liquor pretreatment achieves only minor delignification relative to traditional kraft pulping with oxygen delignification . Kraft pulping of biomass encompasses white liquor (NaOH + Na 2 S) cook and O 2 treatment for delignification prior to enzymatic hydrolysis for monomeric sugar production.…”
Section: Methodsmentioning
confidence: 99%
“…Green liquor pretreatment achieves only minor delignification relative to traditional kraft pulping with oxygen delignification . Kraft pulping of biomass encompasses white liquor (NaOH + Na 2 S) cook and O 2 treatment for delignification prior to enzymatic hydrolysis for monomeric sugar production.…”
Section: Methodsmentioning
confidence: 99%
“…One example of this conversion is the reorientation of closed Kraft pulp mills to bioethanol production [23,24]. Wu et al (2014) evaluated the techno-economic potential of repurposing a Kraft mill for bioethanol production from loblolly pine [173]. Fornell et al (2012) discussed the energy efficiency and performed an economic analysis of a conceptual Kraft pulp mill that was converted into a lignocellulosic ethanol plant [174,175].…”
Section: Converting Pulp and Paper Mills Into Biorefineriesmentioning
confidence: 99%
“…As examples, the combination of enzymes recycling and decreases in hydrolysis time led to decreased ethanol production cost by 27% for hardwoods and 38% for softwood feedstocks (Gregg et al, 1998). The co-location of the bioethanol plant into a softwood kraft-pulping mill, using the kraft process plus oxygen delignification as pretreatment were also shown to result in economic production of bioethanol (Wu et al, 2014). More specifically, an economic analysis showed that through such implementations, an ethanol yield of 285 L/ton of dry wood with a total production cost of USD 0.55/L could be obtained (Wu et al, 2014).…”
Section: Technical and Economic Aspects Of Bioethanol Productionmentioning
confidence: 99%
“…The co-location of the bioethanol plant into a softwood kraft-pulping mill, using the kraft process plus oxygen delignification as pretreatment were also shown to result in economic production of bioethanol (Wu et al, 2014). More specifically, an economic analysis showed that through such implementations, an ethanol yield of 285 L/ton of dry wood with a total production cost of USD 0.55/L could be obtained (Wu et al, 2014). In this sense, it would be interesting to evaluate how the incorporation of a different pretreatment to a different raw material (like pin-chips or sawdust) would work, taking advantage of the existing infrastructure of the mill.…”
Section: Technical and Economic Aspects Of Bioethanol Productionmentioning
confidence: 99%